2007
DOI: 10.1007/s12149-007-0054-7
|View full text |Cite
|
Sign up to set email alerts
|

SPECT evaluation of cerebral blood flow during arm exercise in patients with subclavian steal

Abstract: Our results suggest that subclavian steal is a benign condition in asymptomatic patients. On the other hand, arm exercise-induced rCBF reduction can occur in the cerebrum and cerebellum in patients with VBI symptoms possibly related to low CVR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The reproducibility and accuracy of the rCBF values obtained using the 3DSRT method have already been reported [16][17][18][19][20][21]. It is thought to be important to understand the differences in the rCBF values obtained using the 3DSRT method and the manual tracing method before the 3DSRT method is widely used.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The reproducibility and accuracy of the rCBF values obtained using the 3DSRT method have already been reported [16][17][18][19][20][21]. It is thought to be important to understand the differences in the rCBF values obtained using the 3DSRT method and the manual tracing method before the 3DSRT method is widely used.…”
Section: Discussionmentioning
confidence: 93%
“…Then, the rCBF value in each segment is automatically measured. A number of studies have already demonstrated the reproducibility and accuracy of the rCBF values obtained using the 3DSRT method [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The 3DSRT was performed by a consecutive analyzing process as follows: 1) anatomical standardization using the SPM99 algorithm, 2) analysis using constant 318 ROIs divided into 12 groups (segments) in each hemisphere, 3) calculation of the area-weighted average for each of the respective 24 segments based on the value in each ROI, and 4) display of the results followed by the saving of respective values of the 636 ROIs (both hemispheres) in the CVS file format. These ROIs were categorized into 12 segments in the template (12) (callosomarginal, pericallosal, precentral, central, parietal, angular, temporal, lenticular nucleus, posterior, thalamus, hippocampus, and cerebellum) according to the arterial supply (anterior, middle, posterior, and vertebral cerebral artery territory) (10). In this study, the results are expressed as the mean Ϯ SD of right SPECT-CBF in these segments.…”
Section: Subjects As Shown In Tablementioning
confidence: 99%